2009
DOI: 10.1002/cncr.24309
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomaviruses are identified in a subgroup of sinonasal squamous cell carcinomas with favorable outcome

Abstract: BACKGROUND:The role of human papillomavirus (HPV) in the pathogenesis of squamous cell carcinomas (SCCs) of the sinonasal tract and its clinicopathological implications were evaluated.METHODS:All SCCs of the sinonasal tract diagnosed in the Hospital Clinic of Barcelona from 1981 to 2006 were retrospectively evaluated (N = 60). Clinical and pathological data were reviewed. HPV infection was determined and typed by amplification of HPV DNA by polymerase chain reaction using the SPF‐10 primers. p16INK4a expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
149
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 86 publications
(120 reference statements)
12
149
5
1
Order By: Relevance
“…Due to these growth patterns, while the diagnosing pathologist could consider if NKSCC or papillary SCC represent malignant transformation of an inverted papilloma, both of these SCC types consist of diffuse, full thickness, overtly carcinomatous tumor, rather than being mixed with lower grade areas or with foci of actual inverted papilloma. Further, the SCCs that arise from inverted papillomas are almost always keratinizingtype SCC and not NK or papillary SCC [20].…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these growth patterns, while the diagnosing pathologist could consider if NKSCC or papillary SCC represent malignant transformation of an inverted papilloma, both of these SCC types consist of diffuse, full thickness, overtly carcinomatous tumor, rather than being mixed with lower grade areas or with foci of actual inverted papilloma. Further, the SCCs that arise from inverted papillomas are almost always keratinizingtype SCC and not NK or papillary SCC [20].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Stoddard et al [28] recently studied inverted papillomas using RNA in situ hybridization for high risk HPV and found that all 19 papillomas were positive, but most at very low signal levels. Further, as it turns out, when closely examining the studies on transcriptionally-active high risk HPV in sinonasal SCC, the subset of 27 patients with inverted papilloma-related SCC had active HPV in only 2 cases (7.4 %) [7,20]. This suggests that the high risk HPV may be important for the growth of inverted papillomas and perhaps for carcinogenesis within them, but that it typically does not drive the growth of established tumors as it does in SCC of the oropharynx.…”
Section: Human Papillomavirusmentioning
confidence: 99%
“…SCC arising ex-inverted papillomas also reveal HPV RNA transcription, and evidence of viral integration [66]. [97]. There are limited data regarding sinonasal HPV ''carrier'' rates.…”
Section: Hpv In Other Laryngeal Lesionsmentioning
confidence: 99%
“…Good correlation between HPV? status, detected by either PCR or ISH, and diffuse p16 overexpression, has been reported in sinonasal SCC, albeit in small numbers [97,[119][120][121]. Strong diffuse p16 expression cannot be accepted as a surrogate HPV biomarker in any untested context, as this pattern of overexpression has also been detected in HPV-negative sinonasal undifferentiated carcinoma [122].…”
Section: Hpv and Sinonasal Cancermentioning
confidence: 99%
“…[16][17][18] Infection with high-risk HPV has been associated with malignant transformation, and causally related to cervical cancer 19,20 and a subset of squamous cell carcinomas in the head and neck and anogenital region different from the cervix. [21][22][23] Verrucous carcinoma has been associated with both low-risk (types 6 and 11) and high-risk (types 16 and 18) types of HPV. 18,24,25 However, a causal relationship between HPV and verrucous carcinoma remains to be proven, specifically in those cases in which a low-risk HPV has been suggested to be involved in the genesis of the tumours.…”
mentioning
confidence: 99%